2014
DOI: 10.1111/dme.12376
|View full text |Cite
|
Sign up to set email alerts
|

The use of oral hypoglycaemic agents in pregnancy

Abstract: While insulin has been the treatment of choice when lifestyle measures do not maintain glycaemic control during pregnancy, recent studies have suggested that certain oral hypoglycaemic agents may be safe and acceptable alternatives. With the exception of metformin and glibenclamide (glyburide), there are insufficient data to recommend treatment with any other oral hypoglycaemic agent during pregnancy. There are no serious safety concerns with metformin, despite it crossing the placenta. When used in the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 68 publications
1
26
0
3
Order By: Relevance
“…Furthermore, potential advantages are associated with the use of metformin compared with insulin to treat hyperglycaemia, including, consistently less gestational weight gain (pooled mean difference −1.14 kg; 95% CI −2.22 to −0.006), increased levels of self-reported maternal satisfaction (evaluated using questionnaires) and a reduced incidence of neonatal hypoglycaemia (pooled risk ratio 0.78 (95% CI 0.60-1.01)) in pregnant women 75,76 . PCOS is characterized by hyperandrogenism, hyperinsulinaemia and polycystic ovaries 77 .…”
Section: Pharmacological Preventionmentioning
confidence: 99%
“…Furthermore, potential advantages are associated with the use of metformin compared with insulin to treat hyperglycaemia, including, consistently less gestational weight gain (pooled mean difference −1.14 kg; 95% CI −2.22 to −0.006), increased levels of self-reported maternal satisfaction (evaluated using questionnaires) and a reduced incidence of neonatal hypoglycaemia (pooled risk ratio 0.78 (95% CI 0.60-1.01)) in pregnant women 75,76 . PCOS is characterized by hyperandrogenism, hyperinsulinaemia and polycystic ovaries 77 .…”
Section: Pharmacological Preventionmentioning
confidence: 99%
“…The prevalence of pregnancy complicated by diabetes and/or gestational diabetes mellitus has been increasing [1]. Hyperglycaemia during pregnancy substantially increases the risk, for both mother and fetus, of developing various complications [2], which can be prevented by vigorous glycaemic control with insulin and/or metformin [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been reports of growth retardation, delayed ossification and miscarriage in pregnant rats and rabbits treated with DPP-4 inhibitors. 9 Studies in rats treated with SGLT-2 inhibitors have shown toxicity in developing kidneys, with an increased incidence and/or severity of renal pelvic and tubular dilatations in the time-period corresponding to the second and third trimesters of human pregnancy. 9 In addition, as mentioned in the labels for DPP-4 inhibitors and SGLT2-inhibitors, these agents have been shown to cross the placenta and to be excreted into breast milk in animal studies.…”
Section: Introductionmentioning
confidence: 99%
“…9 Studies in rats treated with SGLT-2 inhibitors have shown toxicity in developing kidneys, with an increased incidence and/or severity of renal pelvic and tubular dilatations in the time-period corresponding to the second and third trimesters of human pregnancy. 9 In addition, as mentioned in the labels for DPP-4 inhibitors and SGLT2-inhibitors, these agents have been shown to cross the placenta and to be excreted into breast milk in animal studies. However, reports on safety and outcomes in pregnant women who were exposed to these newer glucose-lowering agents are very scarce or non-existing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation